Analisis Faktor-Faktor Marketing Mix Yang Mempengaruhi Keputusan Konsumen Membeli Benih Jagung Hibrida Pioneer P21 Di Kabupaten Bantul - Fatonah, Siti; Soebandiono, R. Sigit (STIE AUB Surakarta)
The development of genetic engineering technology to produce superior hybrids cause competition among producers of hybrid com seeds getting tighter. To win this competition, Indonesia PT. DuPont should consider factors that influence consumer decisions to buy a pioneer of hybrid com seeds (P21) in terms of the marketing mix, that are product, price, promotion and distribution.This research was conducted using a questionnaire with a sample of farmers who had bought and planted the seeds of hybrid corn pioneer (P21) In Bantul Regency. In this research, the researcher used 100 respondents. Validity and rellablllty tests used to measure each item of research variables. Data analysis is done using classical assumption test, then tested by multiple linear regression analysis, t test, F test and test the coefficient of determination.Keywords: decision of pruchasing, product, price, promotion and distribution